Study of Polycystic Ovaries (PCO) in Mymensingh Medical College Hospital, Bangladesh (Journal of Bangladesh College of Physicians and Surgeons, 2015)
Background information: Polycystic ovaries (PCO) and their clinical expression (polycystic ovary syndrome) are conditions characterized by menstrual abnormality, clinical and biochemical features of hyperandrogenism. It is the killer of womanhood. Woman of any ethnic background can present with PCOS.Objectives: To find out demographic characteristics such as age, BMI, clinical presentations like hirsutism, menstrual cycle pattern and fertility status and the hormonal changes like LH/FSH ratio and serum testosterone level.Study design: A descriptive cross sectional study for 1 year from December 2009 to November 2010.Study setting: Outdoor Department of obstetrics and gynaecology and center for Nuclear Medicine and Ultrasonography (CNMU) Mymensingh Medical College Hospital, Mymensingh.Result: Total 55 patients were evaluated. Most common age was 20-29 years (72.7%) with mean age 23.55 years and mean BMI 27.12 kg/m2. Clinical presentations were in this study hirsutism in 36.4%, irregular menstrual cycle in 63.6% and subfertility in 56.3%. Laboratory findings revealed testosterone level was more than normal range in 58% case, LH/FSH ratio was increased (more than 1:1) in 58.2% cases, 26 cases had both increased testosterone level and increased LH/FSH ratio. 17cases had testosterone level within normal range and LH/FSH ratio less than 1:1.Conclusion: There are significant relationship between irregular menstrual cycle pattern and hormonal changes such as testosterone level and LH/FSH ratio. There are also significant relationship between BMI and hirsutism with increased testosterone level.J Bangladesh Coll Phys Surg 2014; 32: 142-148